2014
DOI: 10.1007/s11211-014-0216-4
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Errors in the Averseness of Apologizing

Abstract: Apologizing is often seen as the appropriate response after a transgression for perpetrators. Yet, despite the positive effects that apologies elicit after situations of conflict, they are not always delivered easily. We argue that this is due -at least in part-to perpetrators overestimating the averseness of apologizing, thus committing a forecasting error. Across two laboratory experiments and one autobiographical recall study, we demonstrate that perpetrators overestimate the averseness they will experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
(79 reference statements)
0
19
0
Order By: Relevance
“…For instance, in an autobiographical recall study (Chaudhry & Loewenstein, 2017), we found that interpersonal conflict can be the result of failing to thank and failing to apologize, and that these omissions stem from not fully appreciating their value to the other party. In other work, it has been demonstrated that failing to apologize can indeed be driven by perpetrators’ misestimation of the costs and benefits of apologizing: They tend to overestimate the costs and underestimate the benefits of apologizing (Leunissen, De Cremer, van Dijke, & Folmer, 2014). As long as the basic setup applies, RET offers a framework that can help navigate a host of situations involving interpersonal communication and conflict.…”
Section: Tests Of the Predictionsmentioning
confidence: 99%
“…For instance, in an autobiographical recall study (Chaudhry & Loewenstein, 2017), we found that interpersonal conflict can be the result of failing to thank and failing to apologize, and that these omissions stem from not fully appreciating their value to the other party. In other work, it has been demonstrated that failing to apologize can indeed be driven by perpetrators’ misestimation of the costs and benefits of apologizing: They tend to overestimate the costs and underestimate the benefits of apologizing (Leunissen, De Cremer, van Dijke, & Folmer, 2014). As long as the basic setup applies, RET offers a framework that can help navigate a host of situations involving interpersonal communication and conflict.…”
Section: Tests Of the Predictionsmentioning
confidence: 99%
“…For example, even though victims want apologies after intentional transgressions, perpetrators are actually more likely to apologize after unintentional rather than intentional transgressions because of the guilt that they feel (Leunissen et al, ). Transgressors also overestimate how aversive it would be to apologize (Leunissen, de Cremer, van Dijke, & Reinders Folmer, ), suggesting that transgressors are reticent to apologize and even when they do, it is not necessarily when victims want it. Finally, victims underestimate transgressors' desires for forgiveness, and because victims' beliefs that transgressors want to be forgiven correlate with their actual propensity to forgive, such miscalibrations have important implications for eventual conflict resolution (Adams & Inesi, ).…”
Section: Asymmetric Desires For Justice Restorationmentioning
confidence: 99%
“…Nevertheless, perpetrators may be reluctant to offer an apology for a variety of reasons. For example, they may be motivated to protect their self-image or may be pessimistic that their apology will be appreciated by, or elicit forgiveness from, the victim (Leunissen, De Cremer, Van Dijke, & Reinders Folmer, 2014;Okimoto, Wenzel, & Hedrick, 2013;Sedikides & Gregg, 2008).…”
mentioning
confidence: 99%